On the Complexity of Visual Judgement of Kinship. (May 2019) - Brodo, Linda; Grosso, Enrico
Discrimination of close relatives is a basic ability of humans, with demonstrated and important consequences in social and sexual behaviours. In this article, we investigate the visual judgement of kinship, that is the process of discriminating relatives based on visual cues and, in particular, on facial resemblance. Starting from triplets of face stimuli, we focus on a simple two-alternative forced choice protocol and we ask participants to evaluate kinship, similarity, or dissimilarity. Response times of the participants performing these visual judgements are recorded and further analysed. The analysis can also benefit from previous findings on the adopted face data set; in particular, results are compared with reference to an independently generated and statistically reliable similarity index, which is available for each possible considered pair of images. Our results confirm previous findings stating that kinship and similarity judgements are closely related and take longer, on average, than dissimilarity judgement. Moreover, they confirm that similarity and dissimilarity cannot be considered just as opposite concepts, and strongly support the existence of different pathways for similarity and dissimilarity judgements. Concerning kinship judgements, results confirm the assumption, inherent in previous models, of a close relationship between cues signalling for kinship and cues signalling for similarity but suggest the existence of a more complex process, where dissimilarity cues need to be explicitly included in order to model measured effects. Our results reinforce the idea that modulation mechanisms between similarity and dissimilarity measures could explain selective suppression or enhancement effects reported in previous works. A new framework is thus proposed hypothesising that kinship recognition is the result of a balanced evaluation of both similar or dissimilar pathways.